Stabilty derivatives in the newtonian limit - Crasta, Asha; Khan, Sher Afghan (International Association of Engineering and Management Education (IAEME), 2013)
This paper presents an analytical method to predict the aerodynamic stability derivatives of oscillating delta wings with curved leading edge. It uses the Ghosh similitude and the strip theory to obtain the expressions for stability derivatives in pitch and roll in the Newtonian limit. The present theory gives a quick and approximate method to estimate the stability derivatives which is very handy at the design stage. They are applicable for wings of arbitrary plan form shape at high angles of attack provided the shock wave is attached to the leading edge of the wing. The expressions derived for stability derivatives become exact in the Newtonian limit. The stiffness derivative and damping derivative in pitch and roll are dependent on the geometric parameter of the wing. It is found that stiffness derivative linearly varies with the amplitude. Whenever, the plan form area is increased the stiffness derivative is also increased and vice versa. There is a shift of the center of pressure towards the trailing edge whenever wing plan form is changed from concave to convex plan form. In the case of damping derivative since expressions for these derivatives are non-linear and the same is reflected in all the results. Good agreement is found with existing theories in some special cases.